Oil-soluble demulsifier and preparation method thereof

By adding block polymer and adsorption filler to the deemulsion agent, an ionic system is formed, which solves the problem of deemulsion efficiency reduction caused by re-aggregation of micro-oil droplets after deemulsion of the existing deemulsion agent, and achieves efficient deemulsion effect and supports multiple recycling.

CN119529882BActive Publication Date: 2025-04-18SHANDONG HUAYOU WANDA CHEMICAL CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510107945.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

After demulsification, the micro-oil droplets are difficult to accumulate after demulsification, resulting in a decrease in the efficiency of demulsification and unable to meet market demand.

Method used

The block polymer and adsorption filler are added to the deemulsifier system. By recombining the sulfonic acid group in the block polymer with the imidazolium group in the adsorption filler, an ionic system is formed, which enhances the adsorption characteristics of the adsorption filler and avoids the reversible conversion between deemulsification and emulsification.

Benefits of technology

It effectively improves the demulsification rate of oil-soluble demulsifiers, ensuring that good demulsification efficiency can be maintained after multiple recycles, and due to the presence of magnetic iron tetroxide, the demulsifier can be recycled and reused.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of oil extraction, and in particular to an oil-soluble demulsifier and a preparation method thereof. The oil-soluble demulsifier comprises the following raw materials in parts by weight: 8-9 parts of a block polymer, 2-3 parts of an adsorbent filler and 80-90 parts of water. The block polymer and the adsorbent filler are added to the demulsifier system, thereby solving the problem of reduced demulsification efficiency caused by re-aggregation of micro-oil droplets after demulsification of a ternary composite flooding produced water system by an existing demulsifier, and the oil-soluble demulsifier can still maintain good demulsification efficiency after multiple cycles of use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petroleum extraction, and in particular to an oil-soluble demulsifier and a preparation method thereof. Background Art

[0002] With the continuous exploitation of oil, the emulsification degree of the produced water system of ASP flooding gradually increases. The oil droplets are fine in size, stable in nature and difficult to separate, so they need to be demulsified. Although the commonly used demulsifiers have good demulsification effects, the micro oil droplets are difficult to aggregate after demulsification, resulting in a reversible system between demulsification and emulsification, which reduces the demulsification efficiency and cannot meet market demand. Summary of the invention

[0003] The object of the present invention is to provide an oil-soluble demulsifier and a preparation method thereof, by adding a block polymer and an adsorbent filler into the demulsifier system, thereby solving the problem of reduced demulsification efficiency caused by reaggregation of micro-oil droplets after demulsification of the produced water system of ASP flooding by the existing demulsifier, and at the same time, the demulsifier can still maintain good demulsification efficiency after multiple cycles of use;

[0004] The object of the present invention can be achieved by the following technical scheme: A method for preparing an oil-soluble demulsifier, comprising the following steps: weighing the following raw materials by weight: 8-9 parts of a block polymer, 2-3 parts of an adsorbent filler and 80-90 parts of water, mixing the block polymer, the adsorbent filler and the water to prepare an oil-soluble demulsifier;

[0005] The block polymer is prepared by the following steps:

[0006] Step A1: Mix itaconic anhydride and cardanol, stir at a rate of 100-120 rpm and a temperature of 90° C., add sodium acetate, and react for 3-4 hours to obtain intermediate 1; mix intermediate 1 and diethanolamine, stir at a rate of 180-240 rpm and a temperature of 60° C., react for 4-5 hours, then add acryloyl chloride, and continue to react for 8-10 hours to obtain intermediate 2;

[0007] The dosage ratio of itaconic anhydride, cardanol and sodium acetate is 0.18-0.19 mol: 0.16-0.18 mol: 8-10 mL; the dosage ratio of intermediate 1, diethanolamine and acryloyl chloride is 0.2-0.21 mol: 0.1 mol: 0.1-0.12 mol;

[0008] During the reaction, under the condition of sodium acetate as a catalyst, the hydroxyl group in cardanol reacts with the anhydride group in itaconic anhydride to form an ester group and generate a carboxyl group to obtain intermediate 1. The carboxyl group in intermediate 1 reacts with the hydroxyl group in diethanolamine to form an ester group to obtain intermediate 2.

[0009] Step A2: Sodium bisulfite and deionized water are mixed, stirred at a stirring rate of 200-240 rpm and a temperature of 120° C., and intermediate 2 is added, and the reaction is carried out for 3-4 hours to obtain intermediate 3; intermediate 3, mercaptosilicone oil, azobisisobutyronitrile and butyl acetate are mixed, and the reaction is carried out for 1-2 hours at a stirring rate of 180-200 rpm and a temperature of 75° C. to obtain a block polymer;

[0010] The dosage ratio of sodium bisulfite, deionized water and intermediate 2 is 0.04-0.045 mol: 10-12 mL: 0.015-0.018 mol; the dosage ratio of intermediate 3, mercapto silicone oil, azobisisobutyronitrile and butyl acetate is 0.01-0.012 mol: 15-18 g: 0.12-0.15 g: 30-32 mL;

[0011] During the reaction, under the action of sodium bisulfite, the double bond in the itaconic anhydride structure of intermediate 2 is sulfonated to form a sulfonic acid group to obtain intermediate 3. Then, under the action of azobisisobutyronitrile, the unsulfonated double bond in intermediate 3 reacts with the thiol group in the thiol silicone oil and polymerizes to obtain a block polymer.

[0012] The adsorption filler is prepared by the following steps:

[0013] Step B1: ferric chloride hexahydrate, sodium acetate, polyethylene glycol and ethylene glycol are mixed, stirred at a stirring rate of 140-150 rpm and a temperature of 70° C. for 15-20 min, then sodium montmorillonite is added and ultrasonically dispersed for 30 min, the temperature is raised to 200° C., and the reaction is carried out for 4-5 h to obtain a precursor 1;

[0014] The dosage ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, ethylene glycol and sodium montmorillonite is 3.4-3.5 g: 9.4-9.5 g: 2.5-2.6 g: 90-110 mL: 2.5-2.6 g;

[0015] During the reaction, the precursor 1 was prepared by using a solvothermal method with ferric chloride hexahydrate as the iron source and the active hydroxyl groups on the surface of the sodium-montmorillonite, thereby forming magnetic ferrosoferric oxide on the surface of the sodium-montmorillonite.

[0016] Step B2: zinc nitrate hexahydrate, precursor 1 and methanol are mixed and ultrasonically dispersed for 15 minutes, stirred at a stirring rate of 100-120 rpm and a temperature of 60° C. for 15-20 minutes, then heated to 90° C. and 2-methylimidazole is added, reacted for 6-8 hours, to obtain precursor 2;

[0017] The dosage ratio of zinc nitrate hexahydrate, precursor 1, 2-methylimidazole and methanol is 0.1-0.11 mol: 0.4-0.45 g: 0.8-0.85 mol: 40-45 mL;

[0018] During the reaction, a solvent thermal method is used, with zinc nitrate hexahydrate as a zinc source and 2-methylimidazole as a ligand. Since the surface of the precursor 1 contains a large number of oxygen-containing groups, the oxygen-containing groups capture positively charged zinc ions and then coordinate with the 2-methylimidazole to form a coordination bond, thereby forming a metal organic framework structure on the surface of the precursor 1 and growing it to obtain the precursor 2.

[0019] Step B3: Mix carbon nanotubes, ethanol and deionized water and ultrasonically disperse for 15-20 minutes, adjust the pH value to 4, stir and add γ-glycidyloxypropyltrimethoxysilane at a stirring rate of 300-350rpm and a temperature of 110°C, and react for 4-6 hours to obtain modified carbon nanotubes, mix precursor 2, modified carbon nanotubes and methanol, and react for 5-6 hours at a stirring rate of 600-700rpm and a temperature of 95°C to obtain an adsorption filler;

[0020] The ratio of carbon nanotubes to γ-glycidyloxypropyltrimethoxysilane is 1-1.1 g: 0.12-0.15 g; the ratio of precursor 2, modified carbon nanotubes and methanol is 1.25-1.3 g: 0.45-0.5 g: 15-20 mL;

[0021] During the reaction, the carbon nanotubes are modified with γ-glycidyloxypropyltrimethoxysilane to introduce epoxy groups to obtain modified carbon nanotubes, and then the epoxy groups react with the imidazole groups in the precursor 1 to form imidazolium structures to obtain adsorption fillers;

[0022] Beneficial effects of the invention: The invention discloses an oil-soluble demulsifier and a preparation method thereof. By adding a block polymer and an adsorbent filler into the demulsifier system, the problem of reduced demulsification efficiency caused by reaggregation of micro-oil droplets after demulsification of a ternary composite flooding produced water system by an existing demulsifier is solved, and the demulsification efficiency can still be maintained after multiple cycles of use; by compounding a block polymer and an adsorbent filler, during use, since the block polymer contains a large number of sulfonic acid groups, it can be compounded with an adsorbent filler containing an imidazolium group to form an ion system, so that during the use of the oil-soluble demulsifier, the adsorbent filler is first dispersed in the emulsion system with the block polymer and separated from the diffusion, and due to the adsorbent filler, the adsorbent filler is further dispersed in the emulsion system. The attached filler itself is based on montmorillonite, which is hybridized with magnetic ferroferric oxide and carbon nanotubes, and a metal organic structure with a large surface area and adsorption characteristics is formed therein. Due to the effect of carbon nanotubes on the interfacial film in the emulsion system, the adsorption filler itself has a demulsification characteristic. At the same time, the layered structure of montmorillonite itself and the formed metal organic structure make it have good adsorption characteristics for micro oil droplets, avoiding the reversible conversion between demulsification and emulsification, and effectively improving the demulsification rate of the oil-soluble demulsifier. At the same time, due to the presence of magnetic ferroferric oxide, it can be recycled and reused after the demulsification is completed, and due to its own characteristics, it can still maintain good demulsification performance after multiple uses. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 A method for preparing an oil-soluble demulsifier comprises the following steps: weighing the following raw materials by weight: 8 parts of a block polymer, 2 parts of an adsorbent filler and 80 parts of water, mixing the block polymer, the adsorbent filler and the water to prepare an oil-soluble demulsifier;

[0025] The block polymer is prepared by the following steps:

[0026] Step A1: Itaconic anhydride and cardanol were mixed, stirred at a stirring rate of 100 rpm and a temperature of 90°C, and sodium acetate was added for 3 hours to obtain intermediate 1. Intermediate 1 was mixed with diethanolamine, stirred at a stirring rate of 180 rpm and a temperature of 60°C for 4 hours, and acryloyl chloride was added and the reaction was continued for 8 hours to obtain intermediate 2;

[0027] The ratio of itaconic anhydride, cardanol and sodium acetate is 0.18 mol: 0.16 mol: 8 mL; the ratio of intermediate 1, diethanolamine and acryloyl chloride is 0.2 mol: 0.1 mol: 0.1 mol;

[0028] Step A2: Sodium bisulfite and deionized water are mixed, stirred at a stirring rate of 200 rpm and a temperature of 120° C., and intermediate 2 is added, and the reaction is carried out for 3 hours to obtain intermediate 3. Intermediate 3, commercially available KF-2001 mercapto silicone oil, azobisisobutyronitrile and butyl acetate are mixed, and the reaction is carried out for 1 hour at a stirring rate of 180 rpm and a temperature of 75° C. to obtain a block polymer;

[0029] The amount ratio of sodium bisulfite, deionized water and intermediate 2 is 0.04 mol: 10 mL: 0.015 mol; the amount ratio of intermediate 3, mercapto silicone oil, azobisisobutyronitrile and butyl acetate is 0.01 mol: 15 g: 0.12 g: 30 mL;

[0030] The adsorption filler is prepared by the following steps:

[0031] Step B1: ferric chloride hexahydrate, sodium acetate, polyethylene glycol and ethylene glycol were mixed, stirred at a stirring rate of 140 rpm and a temperature of 70° C. for 15 min, and then commercially available Hebei Lingshou sodium-based montmorillonite was added and ultrasonically dispersed for 30 min, and the temperature was raised to 200° C. and reacted for 4 h to obtain a precursor 1;

[0032] The dosage ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, ethylene glycol and sodium montmorillonite is 3.4 g: 9.4 g: 2.5 g: 90 mL: 2.5 g;

[0033] Step B2: zinc nitrate hexahydrate, precursor 1 and methanol were mixed and ultrasonically dispersed for 15 minutes, stirred at a stirring rate of 100 rpm and a temperature of 60° C. for 15 minutes, then heated to 90° C. and 2-methylimidazole was added, and reacted for 6 hours to obtain precursor 2;

[0034] The dosage ratio of zinc nitrate hexahydrate, precursor 1, 2-methylimidazole and methanol is 0.1 mol: 0.4 g: 0.8 mol: 40 mL;

[0035] Step B3: Mix commercially available source leaf S27458 carbon nanotubes, ethanol and deionized water and ultrasonically disperse for 15 minutes, adjust the pH value to 4, stir and add γ-glycidyloxypropyltrimethoxysilane at a stirring rate of 300 rpm and a temperature of 110°C, and react for 4 hours to obtain modified carbon nanotubes, and mix the precursor 2, the modified carbon nanotubes and methanol, and react for 5 hours at a stirring rate of 600 rpm and a temperature of 95°C to obtain an adsorption filler;

[0036] The amount ratio of carbon nanotubes to γ-glycidyloxypropyltrimethoxysilane is 1 g:0.12 g; the amount ratio of precursor 2, modified carbon nanotubes and methanol is 1.25 g:0.45 g:15 mL.

[0037] Example 2 A method for preparing an oil-soluble demulsifier comprises the following steps: weighing the following raw materials by weight: 8 parts of a block polymer, 3 parts of an adsorbent filler and 80 parts of water, mixing the block polymer, the adsorbent filler and the water to prepare an oil-soluble demulsifier;

[0038] The block polymer is prepared by the following steps:

[0039] Step A1: Itaconic anhydride and cardanol were mixed, stirred at a stirring rate of 120 rpm and a temperature of 90°C, and sodium acetate was added for 3 hours to obtain intermediate 1. Intermediate 1 was mixed with diethanolamine, stirred at a stirring rate of 180 rpm and a temperature of 60°C for 5 hours, and acryloyl chloride was added and the reaction was continued for 8 hours to obtain intermediate 2;

[0040] The ratio of itaconic anhydride, cardanol and sodium acetate is 0.19 mol: 0.16 mol: 10 mL; the ratio of intermediate 1, diethanolamine and acryloyl chloride is 0.2 mol: 0.1 mol: 0.12 mol;

[0041] Step A2: Sodium bisulfite and deionized water are mixed, stirred at a stirring rate of 200 rpm and a temperature of 120° C., and intermediate 2 is added, and the reaction is carried out for 4 hours to obtain intermediate 3. Intermediate 3, commercially available KF-2001 mercapto silicone oil, azobisisobutyronitrile and butyl acetate are mixed, and the reaction is carried out for 1 hour at a stirring rate of 200 rpm and a temperature of 75° C. to obtain a block polymer;

[0042] The amount ratio of sodium bisulfite, deionized water and intermediate 2 is 0.04 mol: 12 mL: 0.015 mol; the amount ratio of intermediate 3, mercapto silicone oil, azobisisobutyronitrile and butyl acetate is 0.012 mol: 15 g: 0.15 g: 30 mL;

[0043] The adsorption filler is prepared by the following steps:

[0044] Step B1: ferric chloride hexahydrate, sodium acetate, polyethylene glycol and ethylene glycol were mixed, stirred at a stirring rate of 150 rpm and a temperature of 70° C. for 15 min, and then commercially available Hebei Lingshou sodium-based montmorillonite was added and ultrasonically dispersed for 30 min, and the temperature was raised to 200° C. and reacted for 5 h to obtain a precursor 1;

[0045] The dosage ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, ethylene glycol and sodium montmorillonite is 3.4 g: 9.5 g: 2.5 g: 110 mL: 2.5 g;

[0046] Step B2: zinc nitrate hexahydrate, precursor 1 and methanol were mixed and ultrasonically dispersed for 15 minutes, stirred at a stirring rate of 120 rpm and a temperature of 60° C. for 15 minutes, then heated to 90° C. and 2-methylimidazole was added, and reacted for 8 hours to obtain precursor 2;

[0047] The ratio of zinc nitrate hexahydrate, precursor 1, 2-methylimidazole and methanol is 0.1 mol: 0.45 g: 0.85 mol: 40 mL;

[0048] Step B3: Mix commercially available source leaf S27458 carbon nanotubes, ethanol and deionized water and ultrasonically disperse for 15 minutes, adjust the pH value to 4, stir at a stirring rate of 350 rpm and a temperature of 110°C, stir and add γ-glycidyloxypropyltrimethoxysilane, react for 6 hours to obtain modified carbon nanotubes, mix precursor 2, modified carbon nanotubes and methanol, and react for 5 hours at a stirring rate of 700 rpm and a temperature of 95°C to obtain an adsorption filler;

[0049] The amount ratio of carbon nanotubes to γ-glycidyloxypropyltrimethoxysilane is 1 g:0.15 g; the amount ratio of precursor 2, modified carbon nanotubes and methanol is 1.25 g:0.5 g:20 mL.

[0050] Example 3 A method for preparing an oil-soluble demulsifier comprises the following steps: weighing the following raw materials by weight: 9 parts of a block polymer, 3 parts of an adsorbent filler and 90 parts of water, mixing the block polymer, the adsorbent filler and the water to prepare an oil-soluble demulsifier;

[0051] The block polymer is prepared by the following steps:

[0052] Step A1: Itaconic anhydride and cardanol were mixed, stirred at a stirring rate of 120 rpm and a temperature of 90°C, and sodium acetate was added for 4 hours to obtain intermediate 1. Intermediate 1 was mixed with diethanolamine, stirred at a stirring rate of 240 rpm and a temperature of 60°C for 5 hours, and acryloyl chloride was added and the reaction was continued for 10 hours to obtain intermediate 2;

[0053] The ratio of itaconic anhydride, cardanol and sodium acetate is 0.19 mol: 0.18 mol: 10 mL; the ratio of intermediate 1, diethanolamine and acryloyl chloride is 0.21 mol: 0.1 mol: 0.12 mol;

[0054] Step A2: Sodium bisulfite and deionized water are mixed, stirred at a stirring rate of 240 rpm and a temperature of 120° C., and intermediate 2 is added, and the reaction is carried out for 4 hours to obtain intermediate 3. Intermediate 3, commercially available KF-2001 mercapto silicone oil, azobisisobutyronitrile and butyl acetate are mixed, and the reaction is carried out for 2 hours at a stirring rate of 200 rpm and a temperature of 75° C. to obtain a block polymer;

[0055] The amount ratio of sodium bisulfite, deionized water and intermediate 2 is 0.045 mol: 12 mL: 0.018 mol; the amount ratio of intermediate 3, mercapto silicone oil, azobisisobutyronitrile and butyl acetate is 0.012 mol: 18 g: 0.15 g: 32 mL;

[0056] The adsorption filler is prepared by the following steps:

[0057] Step B1: ferric chloride hexahydrate, sodium acetate, polyethylene glycol and ethylene glycol were mixed, stirred at a stirring rate of 150 rpm and a temperature of 70° C. for 20 min, and then commercially available Hebei Lingshou sodium-based montmorillonite was added and ultrasonically dispersed for 30 min, and the temperature was raised to 200° C. and reacted for 5 h to obtain a precursor 1;

[0058] The dosage ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, ethylene glycol and sodium montmorillonite is 3.5 g: 9.5 g: 2.6 g: 110 mL: 2.6 g;

[0059] Step B2: zinc nitrate hexahydrate, precursor 1 and methanol were mixed and ultrasonically dispersed for 15 minutes, stirred at a stirring rate of 120 rpm and a temperature of 60° C. for 20 minutes, then heated to 90° C. and 2-methylimidazole was added, and reacted for 8 hours to obtain precursor 2;

[0060] The ratio of zinc nitrate hexahydrate, precursor 1, 2-methylimidazole and methanol is 0.11 mol: 0.45 g: 0.85 mol: 45 mL;

[0061] Step B3: Mix commercially available source leaf S27458 carbon nanotubes, ethanol and deionized water and ultrasonically disperse for 20 minutes, adjust the pH value to 4, stir at a stirring rate of 350 rpm and a temperature of 110°C, stir and add γ-glycidyloxypropyltrimethoxysilane, react for 6 hours to obtain modified carbon nanotubes, mix precursor 2, modified carbon nanotubes and methanol, stir at a stirring rate of 700 rpm and a temperature of 95°C, react for 6 hours to obtain an adsorption filler;

[0062] The amount ratio of carbon nanotubes to γ-glycidyloxypropyltrimethoxysilane is 1.1 g:0.15 g; the amount ratio of precursor 2, modified carbon nanotubes and methanol is 1.3 g:0.5 g:20 mL.

[0063] Comparative Example 1 Compared with Example 3, this comparative example is different in that the intermediate 3 in the preparation process of the block polymer in Example 3 is replaced by the intermediate 2 in Example 3, and the other steps are the same.

[0064] Comparative Example 2 Compared with Example 3, this comparative example is different in that the adsorption filler in the preparation process of the oil-soluble demulsifier in Example 3 is replaced by the precursor 2 in Example 3, and the other steps are the same.

[0065] Comparative Example 3 Compared with Example 3, this comparative example replaces the adsorption filler in the preparation process of the oil-soluble demulsifier in Example 3 with a commercially available mixture of montmorillonite and carbon nanotubes, wherein the ratio of montmorillonite to carbon nanotubes is 1.3g:0.5g, and other steps are the same.

[0066] Take an oil-soluble demulsifier prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, mix 25 mL of 20# diesel and 500 mL of deionized water, stir and add span80 at a stirring rate of 3000 rpm, stir for 6 hours to prepare an emulsion system, and test its demulsification performance at 25°C and 35°C with reference to SY / T 5281-2000. The amount of demulsifier added is 1000 ppm, and the demulsification time is 5 min. After the test is completed, the demulsifier is recovered using a magnet, and washed with a mixed solution of ethanol and n-hexane in a volume ratio of 1:1, and then ultrasonically cleaned with deionized water for 15 minutes, and the test is repeated. The demulsification performance after recovery is recorded, and its performance retention rate is calculated. The test results are shown in Table 1 below:

[0067] Table 1 Test results

[0068] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Residual moisture content at 25℃ (%) 0.152 0.149 0.142 0.241 0.171 0.579 Residual moisture content at 35℃ (%) 0.117 0.110 0.109 0.219 0.146 0.527 Performance retention rate after 4 times of recycling (%) 96.52 96.73 96.78 90.23 95.51 Cannot be recycled Performance retention rate after 8 cycles (%) 93.18 93.27 93.29 86.72 92.84 Cannot be recycled

[0069] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, the intermediate 3 in the preparation process of the block polymer of Example 3 is replaced by the intermediate 2 of Example 3. Due to the lack of the compound of the imidazolium group and the sulfonic acid group, its performance is reduced. In Comparative Example 2, the adsorption filler in the preparation process of the oil-soluble demulsifier of Example 3 is replaced by the precursor 2 of Example 3. Due to the lack of carbon nanotube grafting, its performance is reduced. In Comparative Example 3, the adsorption filler in the preparation process of the oil-soluble demulsifier of Example 3 is replaced by a commercially available mixture of montmorillonite and carbon nanotubes. Due to the lack of a structure that can adsorb oil droplets, its performance is reduced.

[0070] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

Claims

1. A method for preparing an oil-soluble demulsifier, characterized in that: The method comprises the following steps: weighing the following raw materials by weight: 8-9 parts of block polymer, 2-3 parts of adsorption filler and 80-90 parts of water, mixing the block polymer, adsorption filler and water to prepare an oil-soluble demulsifier; The block polymer is prepared by the following steps: Step A1: Mix itaconic anhydride and cardanol, stir at a rate of 100-120 rpm and a temperature of 90° C., add sodium acetate, and react for 3-4 hours to obtain intermediate 1; mix intermediate 1 and diethanolamine, stir at a rate of 180-240 rpm and a temperature of 60° C., react for 4-5 hours, then add acryloyl chloride, and continue to react for 8-10 hours to obtain intermediate 2; Step A2: Sodium bisulfite and deionized water are mixed, stirred at a stirring rate of 200-240 rpm and a temperature of 120° C., and intermediate 2 is added, and the reaction is carried out for 3-4 hours to obtain intermediate 3; intermediate 3, mercaptosilicone oil, azobisisobutyronitrile and butyl acetate are mixed, and the reaction is carried out for 1-2 hours at a stirring rate of 180-200 rpm and a temperature of 75° C. to obtain a block polymer; The adsorption filler is prepared by the following steps: Step B1: ferric chloride hexahydrate, sodium acetate, polyethylene glycol and ethylene glycol are mixed, stirred at a stirring rate of 140-150 rpm and a temperature of 70° C. for 15-20 min, then sodium montmorillonite is added and ultrasonically dispersed for 30 min, the temperature is raised to 200° C., and the reaction is carried out for 4-5 h to obtain a precursor 1; Step B2: zinc nitrate hexahydrate, precursor 1 and methanol are mixed and ultrasonically dispersed for 15 minutes, stirred at a stirring rate of 100-120 rpm and a temperature of 60° C. for 15-20 minutes, then heated to 90° C. and 2-methylimidazole is added, reacted for 6-8 hours, to obtain precursor 2; Step B3: Mix carbon nanotubes, ethanol and deionized water and ultrasonically disperse them for 15-20 minutes, adjust the pH value to 4, stir and add γ-glycidyloxypropyltrimethoxysilane at a stirring rate of 300-350rpm and a temperature of 110°C, react for 4-6 hours to obtain modified carbon nanotubes, mix precursor 2, modified carbon nanotubes and methanol, react for 5-6 hours at a stirring rate of 600-700rpm and a temperature of 95°C to obtain an adsorption filler.

2. The method for preparing an oil-soluble demulsifier according to claim 1, characterized in that: In step A1: the usage ratio of itaconic anhydride, cardanol and sodium acetate is 0.18-0.19 mol: 0.16-0.18 mol: 8-10 mL; the usage ratio of intermediate 1, diethanolamine and acryloyl chloride is 0.2-0.21 mol: 0.1 mol: 0.1-0.12 mol.

3. The method for preparing an oil-soluble demulsifier according to claim 1, characterized in that: In step A2: the usage ratio of sodium bisulfite, deionized water and intermediate 2 is 0.04-0.045 mol: 10-12 mL: 0.015-0.018 mol; the usage ratio of intermediate 3, mercaptosilicone oil, azobisisobutyronitrile and butyl acetate is 0.01-0.012 mol: 15-18 g: 0.12-0.15 g: 30-32 mL.

4. The method for preparing an oil-soluble demulsifier according to claim 1, characterized in that: In step B1, the usage ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, ethylene glycol and sodium montmorillonite is 3.4-3.5 g: 9.4-9.5 g: 2.5-2.6 g: 90-110 mL: 2.5-2.6 g.

5. The method for preparing an oil-soluble demulsifier according to claim 1, characterized in that: In step B2, the ratio of zinc nitrate hexahydrate, precursor 1, 2-methylimidazole and methanol is 0.1-0.11 mol: 0.4-0.45 g: 0.8-0.85 mol: 40-45 mL.

6. The method for preparing an oil-soluble demulsifier according to claim 1, characterized in that: In step B3: the ratio of carbon nanotubes to γ-glycidyloxypropyltrimethoxysilane is 1-1.1 g: 0.12-0.15 g; the ratio of precursor 2, modified carbon nanotubes and methanol is 1.25-1.3 g: 0.45-0.5 g: 15-20 mL.

7. An oil-soluble demulsifier, characterized in that: Prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Composite absorbent particles for drying an emulsion

    CA2894692A1

  • Polyurethane plastic runway surface spraying material with excellent weather resistance

    CN118440281A